THE ROLE OF TEACHING STYLES IN DRIVING QUALITY OF STUDENT LEARNING AND ACHIEVEMENT: EVIDENCE FROM UNIVERSITIES IN UAE - Jahan, Sarwat; Hijazi, Shadi; Mahdaoui, Wissale (The journal of contemporary issues in business and government, 2021)
Teaching is an art, where the teacher communicates his knowledge using several teaching styles, which facilitates in ensuring that students are presented with an overall learning environment that can further promote their academic achievements and excellence. Though, this has remained the centre of attention for decades, but still studies have frequently overlooked the student’s perspectives that have left a void in the literature.For the very reason, the current investigation has shed light on the role of teaching styles in driving quality of student learning and achievement, where the study has been exclusively limited to Dubai, United Arab Emirates. For the current investigation, the study has presented the qualitative information collected from 10 students based on interpretivism philosophy as it has helped to ensure that the findings of the study are critical in nature, while assuring that the topic of interest (i.e. the role of teacher’s style of students’ achievement, and the provision of quality learning environment) is sufficiently addressed. Considering the latter, the study has considered the use of thematic analysis for the information collected through interviews, where themes were formulated based on the common findings. In reference to the findings, the study has found that teaching style refers to the reasonable combination and application of skills formed by a teacher in long-term teaching practice, which reflects the consistent and stable teaching psychological quality of teachers. In addition, the study also found that students have preferred humorous and rational teaching styles, as the former focuses on two-way communication to keep the classroom atmosphere quite entertaining; whereas the latter focuses upon giving the students a feeling of being relaxed, calm and peaceful environment, where logic prevails over other elements. Hence, both of the teaching styles were found to yield better academic grades and overall achievement of students in their respective domain as they are facilitated to learn in a unique environment.